Case-control study of paternal occupation and childhood leukaemia in Great Britain, 1962-2006. - Keegan, T; Bunch, K; Vincent, T; King, J; O'Neill, K; Kendall, G; MacCarthy, A; Fear, N; Murphy, M (2012)
BACKGROUND: Paternal occupational exposures have been proposed as a risk factor for childhood leukaemia. This study investigates possible associations between paternal occupational exposure and childhood leukaemia in Great Britain. METHODS: The National Registry of Childhood Tumours provided all cases of childhood leukaemia born and diagnosed in Great Britain between 1962 and 2006. Controls were matched on sex, period of birth and birth registration subdistrict. Fathers' occupations were assigned to 1 or more of 33 exposure groups. Social class was derived from father's occupation at the time of the child's birth. RESULTS: A total of 16 764 cases of childhood leukaemia were ascertained. One exposure group, paternal social contact, was associated with total childhood leukaemia (odds ratio 1.14, 1.05-1.23); this association remained significant when adjusted for social class. The subtypes lymphoid leukaemia (LL) and acute myeloid leukaemia showed increased risk with paternal exposure to social contact before adjustment for social class. Risk of other leukaemias was significantly increased by exposure to electromagnetic fields, persisting after adjustment for social class. For total leukaemia, the risks for exposure to lead and exhaust fumes were significantly <1. Occupationally derived social class was associated with risk of LL, with the risk being increased in the higher social classes. CONCLUSION: Our results showed some support for a positive association between childhood leukaemia risk and paternal occupation involving social contact. Additionally, LL risk increased with higher paternal occupational social class.